That's why (you go away) - Michael Learns To Rock; EMI-Casadida Music (Denmark : EMI-Casadida Music, 1995)
Contains three tracks from the album Played On Pepper.
CD 1 : That's Why (You Go Away) / (3:59) -- Time For Changes / (3:54) -- That's Why (You Go Away) (Karaoke Version) / (3:59).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rock music; Songs, English; Popular music